The Comparative Analyzes of the Student's Performance about Matrix in Student Selection Exam (OSS) and the Approved Lecture Books of Ministry for the National Education (MEB) - Aygor, Nilgun; Burhanzade, Hulya (ELSEVIER SCIENCE BV, 2014)
The purpose of this study is to investigate the solving performance of students in the questions of Student Selection Exam (OSS) and the Approved Lecture Books of Ministry for the National Education (MEB). The study used both qualitative and quantitative methods. Sample of the research is 20 students from 2 different classrooms in 11th grade of the 2011-2012 academic years in Adile Mermerci Anatolian High School. To get the information to determine the performance of students for the research, matrix questions gathered from OSS and MEB approved course books. The research has been made in order to prove whether the questions in OSS exam and the questions in MEB approved books are coherent or not. Students are asked to answer 14 questions. The data was analyzed by researchers jointly. The students have difficulties or couldn't even answer the questions of the topics of matrix questions related with logarithm and solving the equations. It had been seen that the questions in MEB books, are similar with the questions that had been published in the OSS Exam. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Student Selection Examination (OSS); The Ministry of National Education (MEB) books; concept of matrix; mathematics education; Education & Educational Research; Linguistics